Role of Cardiac Resynchronization Therapy in addition to optimum medical therapy in Decompensated Heart Failure - Fatema, Nilufar; Haque, KMHS Sirajul; Siddique, Md Abu; Banerjee, Sajal; Hasan, ATM Iqbal; Ahmed, Md Khurshed; Sultan, Md Ahsraf Uddin; Islam, Neena; Arju, Jahanara; Subedi, Bikash; et al. (University Heart Journal, 2010)
Decompensated heart failure is one of the major causes of morbidity and mortality in worldwide. Some of these patients suffer repeatedly after taking optimum medical therapy (OPT). Cardiac resynchronization therapy (CRT) has been shown to be an effective therapy for patients with heart failure and dyssynchrony. DOI: 10.3329/uhj.v5i2.4561 University Heart Journal Vol.5(2) July 2009 pp.79-83